2017
DOI: 10.12973/ejac/80612
|View full text |Cite
|
Sign up to set email alerts
|

Application of Adaptive Neural Fuzzy Inference System and Fuzzy C- Means Algorithm in Simulating the 4-Chlorophenol Elimination from Aqueous Solutions by Persulfate/Nano Zero Valent Iron Process

Abstract: This study investigated the application of adaptive neural fuzzy inference system (ANFIS) and Fuzzy c-means (FCM) algorithm for the simulation and prediction of 4-chlorophenol elimination in aqueous media by the persulfate/Nano zero valent iron process. The structure of developed model which resulted to the minimum value of mean square error was a Gaussian membership function with a total number 10 at input layer, a linear membership function at output layer and a hybrid optimum method, which is a combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Tanhaei et al 28 reported a neuro‐fuzzy modelling of methyl orange removal by magnetic chitosan nanocomposite. Baziar et al 29 applied ANFIS in simulating the sorption of 4‐chlorophenol from aqueous solutions by persulphate/nano zero valent iron process. Ghaedi and Vafaei 30 reviewed the applications of ANN for adsorption of dyes from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Tanhaei et al 28 reported a neuro‐fuzzy modelling of methyl orange removal by magnetic chitosan nanocomposite. Baziar et al 29 applied ANFIS in simulating the sorption of 4‐chlorophenol from aqueous solutions by persulphate/nano zero valent iron process. Ghaedi and Vafaei 30 reviewed the applications of ANN for adsorption of dyes from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, an adaptive neuro-fuzzy inference system (ANFIS) allows for the prediction of water quality parameters, as has been previously demonstrated [37,38]. Additionally, the application of an ANFIS model has been reported to evaluate wastewater treatment processes, namely in the elimination of organic dyes [39,40], oily wastewater [41], chemical additives [36], antibiotics [42] and heavy metals [43,44].…”
Section: Introductionmentioning
confidence: 91%
“…As the photocatalytic process is somewhat affected by different parameters, simulating and modelling based on conventional mathematical approaches are quite complicated [36]. In this context, an adaptive neuro-fuzzy inference system (ANFIS) allows for the prediction of water quality parameters, as has been previously demonstrated [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most well-known methods for determination of persistent organic matter degradation in wastewater treatment is chemical oxygen demand (COD) (Baziar et al, 2018c). Determination of COD in our work is highly important, because of its potential to oxidize the organic pollutants like phenol using dichromate.…”
Section: Cod Removal In Us/io4 -/Fe • Systemmentioning
confidence: 99%